Ambient Pressure Drying as an Advanced Approach to the Synthesis of Silica Aerogel Composite for Building Thermal Insulation. Issue 15 (23rd November 2022) - Boukind, Soumia; Sair, Said; Ait Ousaleh, Hanane; Mansouri, Said; Zahouily, Mohamed; Abboud, Younes; El Bouari, Abdeslam
ABSTRACT: Silica aerogels are the most efficient thermal insulation materials, this property is related essentially to their internal porosity consisting of micro and mesoporous structure. However, their weak mechanical properties and the high cost of drying methods limit the application of these materials. Herein, we propose a facile approach to the development of super-insulating material based on silica aerogel reinforced with alfa nonwoven. The sol-gel process followed by vacuum compression molding was used for composite manufacturing. SEM observations, IR, and Raman spectroscopies have confirmed the good adhesion between the aerogel and nonwoven. Mechanical tests, insulation property, fire resistance, and hydrophobicity are reported and the preliminary results confirm that the aerogel incorporation into the multiscale pores of the nonwoven improves the physical properties of the resulted composite and enhances hydrophobicity without affecting the low thermal conductivity.